2006
DOI: 10.1016/j.jdent.2005.06.004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the air-blowing step on the technique sensitivity of four different adhesive systems

Abstract: KEYWORDSMicrotensile bond strength; Adhesion; Self-etching; All-in-one adhesives; Failure mode; Technique sensitivity Summary Purpose: To evaluate the technique sensitivity of four different adhesive systems using different air-blowing pressure. . Twenty-four extracted molars were used. After grinding the coronal enamel surface, the teeth were divided into two equal groups. The first group's teeth were randomly assigned for bonding with the different adhesives using gentle air-blowing (g). For the teeth of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 11 publications
(11 reference statements)
1
49
0
2
Order By: Relevance
“…10,11,20,21) Water is essential in one-step self-etching systems to ionize acidic monomer enough to dissolve the smear layer and demineralize dentin.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…10,11,20,21) Water is essential in one-step self-etching systems to ionize acidic monomer enough to dissolve the smear layer and demineralize dentin.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,20,21) One-year results of other clinical trials using newly developed one-step self-etch systems showed almost no marginal staining. 3,4) In the present study, enamel beveling and delayed polishing were employed according to the results of our previous laboratory studies, in which significant improvements of marginal sealing of self-etch adhesive systems were demonstrated.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…This was in line with other studies that suggested higher dentin bond strength with SE than with TS in short-term observation. This could be attributed to the lower mechanical properties of TS due to a lower polymerization efficacy, which was a result of incomplete removal of water and solvents 7,11) . Similarly for PB, it was suggested that the absence of photoinitiator in its primer led to a lower polymerization efficacy of the bonding layer 12) .…”
Section: Discussionmentioning
confidence: 99%